Bacillus cereus foodborne outbreaks in mass catering. (June 2018) - Osimani, Andrea; Aquilanti, Lucia; Clementi, Francesca
Highlights: Starchy foods and vegetables produced by mass catering can be a source of B. cereus . B. cereus spore-forming ability must be considered in risk assessment. Temperature abuse of food products allows the production of the emetic toxin. Improper cleaning and inadequate cold chain controls are common risk factors. Training of staff is pivotal for preventing outbreaks. Abstract: Bacillus cereus is the causative agent of two gastrointestinal diseases that cause emesis and diarrhea. As evidenced by the reviewed literature published between 2002 and 2016, the contribution of the catering industry to the spread of B. cereus foodborne intoxications is evident. The reported settings included banquettes, a prison facility, clinics, a wedding, pubs and clubs, a take-away restaurant, a kindergarten, and a hotel restaurant. Many of the reported outbreaks were related to the consumption of rice-based products and starchy foods, together with vegetable-based dishes, with an attack rate that varied between 22.2% and 95.0%. Epidemiological and microbiological investigations allowed the common risk factors to be identified, including incorrect temperature maintenance of the foods and improper cleaning of food production equipment. Hence, to prevent microbial growth and toxin formation, appropriate training of the staff involved in food production and management must be pursued.